Membangun Budaya Organisasi melalui Internalisasi Nilai Spritual dalam Lembaga Pendidikan - Hasan Argadinata; Djum Djum Noor Benty (Proceedings Series of Educational Studies, 2023)
Abstract: Humans are said to be unique creatures with a diversity of personalities and characters that can form a pattern of life order in society. In relation to building superior education, humans in groups work together in an institution or organization led by one person, namely the principal. Each institution has a different style or way of working and usually becomes a characteristic that will later become a positive assumption, belief, or habituation for all members in each institution. The principal has full responsibility and responsibility for the creation of a conducive organizational culture. This study aims to provide an internalization of spiritual values in building organizational culture in educational institutions. Researchers use the literature review method by applying research steps such as topic identification, literature screening, source feasibility, adjusting criteria, describing results, and drawing conclusions. There are five research results: (1) Internalization of the spiritual value of dhuha prayer; (2) Internalization of the spiritual value of reading al-ma'surat and asmaul khusnah; (3) Internalization of the spiritual value of memorizing daily prayers; (4) Internalization of the spiritual value of the tahfidzul Qur'an; (5) Internalization of the spiritual value of congregational prayer during dhuhur and asr.Keywords: organizational culture, educational culture, spiritual values.Abstrak: Manusia dikatakan sebagai makhluk yang unik dengan keanekaragaman kepribadian dan karakter yang dapat membentuk suatu pola tatanan kehidupan di masyarakat. Dalam kaitannya membangun pendidikan yang unggul, manusia secara berkelompok bekerjasama dalam suatu institusi atau organisasi yang dipimpin oleh satu orang yaitu kepala sekolah. Setiap institusi memiliki corak atau cara kerja yang berbeda dan biasanya menjadi ciri khas yang nantinya akan menjadi asumsi, kepercayaan, atau pembiasaan yang bersifat positif bagi seluruh anggota dalam setiap institusi. Kepala sekolah memiliki kewajiban serta tanggungjawab penuh atas penciptaan budaya organisasi yang kondusif. Penelitian ini bertujuan untuk memberikan sebuah internalisasi nilai spiritual dalam membangun budaya organisasi pada lembaga pendidikan. Peneliti menggunakan metode literature review dengan menerapkan langkah-langkah penelitian seperti identifikasi topik, penyaringan literature, kelayakan sumber, penyesuaian kriteria, pendeskripsian hasil, dan penarikan kesimpulan. Terdapat lima hasil penelitian: (1) Internalisasi nilai spiritual sholat dhuha; (2) Internalisasi nilai spiritual membaca al-ma’surat serta asmaul khusnah; (3) Internalisasi nilai spiritual hafalan do’a harian; (4) Internalisasi nilai spiritual tahfidzul Qur’an; (5) Internalisasi nilai spiritual sholat berjama’ah waktu dhuhur dan ashar.Kata kunci: budaya organisasi, budaya pendidikan, nilai spiritual.